Analisa Laju Permukaan Keausan Pada Model Uji Mekanis Bushing Kuningan - Sutarno; Nugrah Rekto Prabowo; Mastur (Accurate: Journal of Mechanical Engineering and Science, 2021)
Bushing is a bearing between movable and immovable components. These spare parts function are to hold the rotating shaft and through the gear box into the shaft which is held by the brass material bushing, where those processes are able to reduce the vibrations and the shock of shock loads. The purpose of this research is to know the level of roughness and wear rate of brass bushing, this research is conducted to find out how efficient it is, the use of a bushing with a field that is very likely to have a large shock load and to know the wear test data, and roughness of the brass bushing. The type of this research used an experimental method. From the results of the study it was concluded that to get the roughness and wear value using a conventional lathe, the spindle rotation was 970 rpm. Based on the experiments with predetermined parameters, the lowest roughness value was Ra 1.13 and the highest roughness was Ra 2.41. In the experiments for the wear test of each specimen, the wear rate obtained after the initial weight was subtracted from the third one hour weight, from the lightest of 0.07 grams and the heviest of 1.62 grams.